Research of vibrations effect on hydraulic valves in military vehicles - Michał Stosiak; Mykola Karpenko; Olegas Prentkovskis; Adam Deptuła; Paulius Skačkauskas (Defence Technology, 2023)
The paper discusses minimizing the effect of external mechanical vibration on hydraulic valves in different military hydraulic drive systems. The current research work presents an analysis of the potential to reduce vibration on the valve casing by installing a valve flexibly on a vibrating surface, i.e., by introducing a material with known stiffness and damping characteristics between the valve casing and the vibrating surface – a steel spring package or special cushions made of elastomer material or of oil-resistant rubber. The article also demonstrates that elastomer cushions placed inside the valve casing – between the casing and the centering springs – can be used as a supplementary or alternative solution in the analyzed method for mitigating the transfer of vibrations. By using materials with appropriately selected elastic and dissipative properties, the effectiveness of vibro-isolation can be increased. The presented theoretical analyzes by linear and non-linear mathematical models have been verified experimentally.